Targeting the macrophage immunocheckpoint: a novel insight into solid tumor immunotherapy - Bei Zhou; Yan Yang; Yan Kang; Jingjing Hou; Yun Yang (Cell Communication and Signaling, 2024)
Abstract Tumor immunotherapy, which targets immune checkpoints, presents a promising strategy for the treatment of various cancer types. However, current clinical data indicate challenges in its application to solid tumors. Recent studies have revealed a significant correlation between the degree of immune response in immunotherapy and the tumor microenvironment, particularly with regard to tumor-infiltrating immune cells. Among these immune cells, macrophages, a critical component, are playing an increasingly vital role in tumor immunotherapy. This review focuses on elucidating the role of macrophages within solid tumors and provides an overview of the progress in immunotherapy approaches centered around modulating macrophage responses through various immune factors. Video Abstract